Aplikasi Teknologi Budidaya Melon (Cucumis melo L.) Kultivar Gama Melon Basket di Lahan Karst Pantai Porok Kabupaten Gunungkidul D.I.Yogyakarta - Budi Setiadi Daryono; Asep Rizal Ibrohim; Sigit Dwi Maryanto (Biogenesis: Jurnal Ilmiah Biologi, 2015)
Melon (Cucumis melo L.) is one of favorite fruits for Indonesian. The fruit is sweet with good odor, and has a high nutrient content. Efforts to increase the production of melon can be reached by improving cultivation technology along with seeds that have better quality, such as resistance to pests and disease, and high production. The low production of melon in farmer fields is often caused by use of local varieties with less improvement technology in crop management. Faculty of Biology has developed a new melon cultivars called Gama Melon Basket. Test the stability of melon cultivars at various enviromental condition have been conducted, except for karst land. Therefore, the stability test of Gama Melon Basket phenotype character cultivated in karst land of Porok Beach of Gunungkidul Yogyakarta is required. The purpose of research was to study stability and uniformity of phenotypic character on Gama Melon Basket cultivar cultivated in karst land of Porok Beach, Gunungkidul, DIY and comparison of its phenotypic characters using modern, intermediate-modern, and traditional methods of cultivation. The research was carried out by cultivating Gama Melon Basket at Coastal Land of Porok Beach with modern, intermediate-modern and traditional cultivation methods. Every week phenotype characters of plants were observed until harvest. Results of quantitative characters of Gama Melon Basket showed that intermediate-modern cultivation method produced highest melon production compare to other methods.The result of Gama Melon Basket using intermediate-modern method is 1552 grams for average weight, fruit circumference is 46,19 cm, fruit diameter is 14,3 cm, fruit length is 14,08 cm, skin thickness is 0,6 cm and thick meat is 0,62 cm. The results revealed that intermediate-modern method is more advisable for melon cultivation in karst land of Porok Beach compared with other methods. Karst Land of Porok Beach has a potential for melon cultivation and production in Gunungkidul.Keywords: Gama Melon Basket, Gunungkidul, karst, phenotype, Porok beach